Intermediate algebra - Weltman, Dennis; Perez, Gilbert (Belmont, California : Wadsworth Pub. Co., 1987)
This text is designed for the student who has completed a course in introductory algebra.
Fundamental Concepts -- Linear Equations and Inequalities -- Polynomials and Factorable Quadratic -- Rational Expressions -- Exponential and Radical Expressions -- Linear Relations and Functions -- Quadratic and higher Order Equations and Inequalities -- Conic Sections -- Systems of Equations -- Exponential and Logarithmic Functions -- Sequences and Series.
Includes index.
Keywords: ALGEBRA